2014
DOI: 10.1038/nature13443
|View full text |Cite
|
Sign up to set email alerts
|

Receptor binding by H10 influenza viruses

Abstract: H10N8 follows H7N9 and H5N1 as the latest in a line of avian influenza viruses that cause serious disease in humans and have become a threat to public health. Since December 2013, three human cases of H10N8 infection have been reported, two of whom are known to have died. To gather evidence relating to the epidemic potential of H10 we have determined the structure of the haemagglutinin of a previously isolated avian H10 virus and we present here results relating especially to its receptor-binding properties, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
89
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(98 citation statements)
references
References 25 publications
7
89
1
1
Order By: Relevance
“…All the H10 chicken viruses and the human isolate had an HA Q220R substitution (residue 210, H3 numbering) relative to the duck viruses. This residue is located in the trimer interface of the HA protein (28). This substitution was shown to increase the pH of virus fusion and viral replication of an H3N2 virus in murine tracheal epithelial cells and lungs of mice (29).…”
Section: Resultsmentioning
confidence: 99%
“…All the H10 chicken viruses and the human isolate had an HA Q220R substitution (residue 210, H3 numbering) relative to the duck viruses. This residue is located in the trimer interface of the HA protein (28). This substitution was shown to increase the pH of virus fusion and viral replication of an H3N2 virus in murine tracheal epithelial cells and lungs of mice (29).…”
Section: Resultsmentioning
confidence: 99%
“…However, surveillance should be emphasized for H10N8 in the event that it acquires new mutations in HA protein as seen for H7N9 between Shanghai-1 and Anhui-1. Recently, Skehel and colleagues 33 examined the receptorbinding properties of an avian H10N2 virus, revealing that the avian H10 virus possesses high avidity for human receptors. The lower avidities observed in our work might reflect the different methods used (for example, under different temperature settings).…”
Section: Discussionmentioning
confidence: 99%
“…In their avian H10/human receptor analogue complex structure, they observed that the residue Q222 of the 220 loop forms a strong hydrogen bond with the human receptor, which is used to explain the phenomenon that avian H10 virus has high avidity for human receptors. Then, based on the similarity of residues in the receptor-binding site of HAs between the avian H10 virus and human-infecting H10 virus, Vachieri et al 33 concluded that the human-infecting H10 virus should possess a high avidity for human receptors. In their humaninfecting H10/human receptor analogue complex structure, they observed that residue R137 forms a 'potential' hydrogen bond with the human receptor, which is helpful for human receptor binding 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, an avian H10N7 strain was found to be the etiological agent responsible for the massive die-off harbor seals in the Baltic Sea, an epidemic that killed more than 10% of the local seal population (4)(5)(6). The receptor binding profile of H10 viruses is currently debated (7)(8)(9)(10)(11)(12), but the subtype has been proven to cause productive infections in humans (13,14). Currently, the only treatment option for patients infected with an H10 subtype influenza virus is the use of antiviral inhibitors that target the viral neuraminidase (NA).…”
mentioning
confidence: 99%